The Involvement of Carbon Monoxide in Mitochondrial Activity and Brain Functions - Mayevsky, Avraham (British Journal of Healthcare and Medical Research, 2024)
The central nervous system is the most sensitive tissue to carbon monoxide and usually receive the greatest lasting damage from CO poisoning. In the current set of experiments, the differences between the physiological responses and the toxic effects were studied. The effects of 1000, 2000 and 3000 ppm CO were studied in rats monitored by a unique multiparametric monitoring system providing information on the hemodynamic, metabolic, ionic and electrical activities in an un-anesthetized state. The effect of cortical spreading depression following the exposure to CO was investigated. The results show that exposure to 1000 ppm CO for 40 minutes doesn’t have a deleterious effect on the resting brain but apparently interfere with metabolic activity during brain activation by cortical spreading depression. Exposure to 2000 ppm CO resulted in elevation of cerebral blood flow. The stability of mitochondrial NADH redox level during CO exposure indicated that tissue hypoxia did not develop. The elevation in blood flow was inhibited by L-nitroarginine methyl ester, indicating that nitric oxide was responsible for the CO-induced elevation in blood flow. Exposure to 2000 ppm CO also triggered a significant decrease in pH and rise in extracellular potassium ion, possibly due to ion-pump inhibition. The amplitude of the electrocorticogram wave activity decreased, indicative of a compromise to physiological activity.